The Many Faces of Edge Intelligence - Ella Peltonen; Ijaz Ahmad; Atakan Aral; Michele Capobianco; Aaron Yi Ding; Felipe Gil-Castineira; Ekaterina Gilman; Erkki Harjula; Marko Jurmu; Teemu Karvonen; Markus Kelanti; Teemu Leppanen; et al. (IEEE Access)
Edge Intelligence (EI) is an emerging computing and communication paradigm that enables Artificial Intelligence (AI) functionality at the network edge. In this article, we highlight EI as an emerging and important field of research, discuss the state of research, analyze research gaps and highlight important research challenges with the objective of serving as a catalyst for research and innovation in this emerging area. We take a multidisciplinary view to reflect on the current research in AI, edge computing, and communication technologies, and we analyze how EI reflects on existing research in these fields. We also introduce representative examples of application areas that benefit from, or even demand the use of EI.